Social Change of Bajo Tribe Society in Karimunjawa: From "Sea Tribe" to "Land Tribe" - Titiek Suliyati (Journal of Maritime Studies and National Integration, 2017)
Known as sea tribe, Bajo tribe is foreigners in Karimunjawa. As a sea tribe, they are nomadic and live on the boat before settling in Karimunjawa. The encouragement to settle in Karimunjawa is due to the fact that the island has a lot of fish and they exploit it to make their living. At the beginning, they live on the boat, but sometimes they move to the land. Later on, they build houses on stilts at coastal areas.The process experienced by Bajo tribe from sea to land tribe is caused by some factors, from the effort to adapt with local people, decreasing number of the captured fish, the government program to make Bajo tribe becomes the land settlers and the change of their livelihood.This research is aimed to study social change occurring to Bajo tribe as a sea tribe that was formerly nomadic into land tribe dwelling in Karimunjawa. Moreover, this research also intended to study the push factors and the impact from the social change toward the life of the settled Bajo society. In line with the problem and the objectives of this research, the qualitative method with the anthropological and sociological approach was used. These two approaches were applied in order to give a better understanding of the social change of Bajo tribe that had already settled in Karimunjawa.The result of the research shows that there is a social change in Bajo society living permanently in Karimunjawa that is, the change of daily behavior in the society, social interaction with other tribes, values held by the society and social institution, structure and social classes. Social change occurring to Bajo society in Karimunjawa brings positive influences. The social changes among others are awareness towards the importance of education, Bajo society has new jobs other than fisherman, the increase of income, living standard, also modernization in fisheries system. The negative impact as a consequence of the social changes is faded culture, changes in life orientation and views of life, and consumerism in the society.